Usulan Perbaikan Postur Dan Fasilitas Kerja Menggunakan Plibel Checklist Dan Quick Exposure Check (Qec) (Studi Kasus: Home Industry Pembuatan Tahu Kusnadi) - Nofirza Nofirza; Suci Anisa Hermayu (UIN Sultan Syarif Kasim Riau, 2016)
Kusnadi's tofu industry is a small-medium industry which engaged in tofu production, where almost all of the production activities doing manually. This research was conducted to evaluate the operator's working posture and make a proposal to repair working facilities towards a working process to minimize the awkward postures. Based on assessment PLIBEL Checklist and Quick Exposure Check (QEC) to operators, it's known that part of neck, shoulders and upper back are having the highest musculoskeletal complaints with 34,62% for Kusnadi's and 30,77% for Dian's. And according to QEC calculation, the score of operator's exposure level at printing station retrieved about 68,18%, at filtering station about 69,31%, and at the cutting station about 56,81%, thus the working posture on that three station need to improve. Results of this research is a proposal in the form of redesign the working facilities, i.e work desk for operators and designing tool in the form of beams and incline at filtering drum using anthropometry data to reduce the occurrence of injury to the operator.Keywords: measurement the load of working posture, PLIBEL checklist, Quick Exposure Check (QEC)